Geriatric Cardiology OSCE: The Hidden Curriculum, Identifying Hypoactive Delirium When Obtaining Procedural Consent - Kathryn Denson; Gabriel Manzi; Judith Rehm; Catharine Malmsten (Association of American Medical Colleges, 2013)
Abstract Fellowship programs must soon comply with the ACGME's Next Accreditation System of milestone performance tracking and reporting requirement, as well as consider entrustable professional activities (EPAs) to measure learner performance. At the Medical College of Wisconsin, geriatricians and cardiologists worked together to create and implement this geriatric cardiology educational objective structured clinical exam (OSCE) for cardiology fellows. Key curriculum content gaps (hypoactive delirium recognition, use of cognitive assessment tools) were identified through cardiology fellow and faculty knowledge/performance gaps on a needs assessment survey. Fellows self-assessed their competency level in those EPAs both pre- and post-OSCE curriculum intervention. Curriculum session included the OSCEs station followed by a debriefing session and evaluation. Results of the post-OSCE session evaluations showed fellows rating "Instructional strategies advanced my learning about geriatrics" as very good (33%) and excellent (66%). Session strengths included "Patient cases are relevant to daily patient care, very realistic," and "Excellent use of the confusion assessment method as a tool to assess delirium." Pre- and post-EPA ratings revealed a shift to competence. The EPA item "I can independently identify delirium using history taking and assessment tools" shifted from 56% competence pre-OSCE to 100% post-OSCE. Our curricular session demonstrated that OSCE is an effective, well-received instructional method to teach and assess fellow EPAs in geriatrics-related ACGME competencies/milestones.